The ozone layer - Bright, Michael; Macdonald, James (New York : Gloucester Press, 1991)
Explains the nature and importance of the ozone layer, how it is most likely damaged, and what measures are being taken to protect it.
"A Watts/Gloucester library edition"--P. [4] of cover.
Includes index.
School Library Journal.
Juvenile literature.
5.3
3-6
Keywords: Chlorofluorocarbons -- Environmental aspects -- Juvenile literature; Ozone layer depletion -- Environmental aspects -- Juvenile literature; Ozone layer -- Juvenile literature; Ozone layer; Ozone layer